Inclusive Strategies in Teaching Speaking: A Narrative Inquiry from an Islamic School in Southern Thailand - Aghna Ilmi Parinduri; Tien Rafida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores how classroom participation is encouraged in an English-speaking class at a dual-curriculum Islamic secondary school in a Muslim-minority area of Southern Thailand. Employing a narrative inquiry design, the research draws on classroom observations, in-depth interviews, and reflective conversations with a teacher to examine how pedagogical choices shape student engagement. The findings show that participation is promoted through three interconnected dimensions: creating psychological safety, using effort-based assessment, and teaching grammar through culturally relevant references. Rather than grouping students by proficiency level, the teacher makes interaction more accessible by normalizing mistakes, incorporating encouragement into grading practices, and connecting language teaching to students’ moral and religious values. However, these strategies are continually adapted to constraints such as large class sizes, diverse proficiency levels, limited instructional time, and fluctuating student motivation. The study highlights that engagement in multilingual, faith-based environments develops through flexible, relational, and context-aware teaching practices. It contributes to discussions on classroom participation and culturally responsive pedagogy in English language education and offers insights for educators in similar minority and religious school settings.